2015
DOI: 10.1007/s10522-015-9627-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent motor unit remodelling in human limb muscles

Abstract: Voluntary control of skeletal muscle enables humans to interact with and manipulate the environment. Lower muscle mass, weakness and poor coordination are common complaints in older age and reduce physical capabilities. Attention has focused on ways of maintaining muscle size and strength by exercise, diet or hormone replacement. Without appropriate neural innervation, however, muscle cannot function. Emerging evidence points to a neural basis of muscle loss. Motor unit number estimates indicate that by age ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 80 publications
(116 reference statements)
9
132
0
2
Order By: Relevance
“…However, we did not find a significant difference in the percentage of NCT in the muscle biopsies. The increased variation in the size of type I fibres and incidence of angular type II fibres observed in our samples and others studying ageing,27 disuse,2 denervation,38 and reinnervation39 is likely a feature of the ongoing denervation–reinnervation process of motor unit remodelling 40. A 12 year follow‐up of older individuals also showed that the decrease in muscle volume was not associated with fibre atrophy,41 adding further evidence that fibre loss is the primary cause of the age‐related decrease in vastus lateralis muscle volume 35…”
Section: Discussionsupporting
confidence: 57%
“…However, we did not find a significant difference in the percentage of NCT in the muscle biopsies. The increased variation in the size of type I fibres and incidence of angular type II fibres observed in our samples and others studying ageing,27 disuse,2 denervation,38 and reinnervation39 is likely a feature of the ongoing denervation–reinnervation process of motor unit remodelling 40. A 12 year follow‐up of older individuals also showed that the decrease in muscle volume was not associated with fibre atrophy,41 adding further evidence that fibre loss is the primary cause of the age‐related decrease in vastus lateralis muscle volume 35…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with this, percentage MyHCI and MyHCIIa levels were greater and lower, respectively, in trained compared with untrained participants (Table 1), irrespective of age [7]. Type IIa and Type IIx muscle fibers are preferentially lost with age as a consequence of failed re-innervation [2]. Accordingly, we report MyHCIIa levels were lower in older compared with younger participants, regardless of training status (Table 1).…”
Section: Resultssupporting
confidence: 74%
“…Each MU comprises a presynaptic motor neuron and a postsynaptic population of mono-innervated skeletal muscle fibers [2]. MUs are, typically but not always [3], defined by uniform skeletal muscle fiber isoform (Type I, Type II) content [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, autophagy was found to be dysregulated in skeletal muscle of aging dogs [12] and humans [11]. It has been determined that caloric restriction and physical exercise are beneficial for rescuing neuromuscular junction fragmentation [2,13,8] and innervation status [2,14], and at the same time reduce impairment of autophagy [11] as well as sarcopenia onset or progression [1518]. This suggests autophagy modulation to be a potential therapeutic target in neuromuscular transmission disorders (Fig.…”
Section: Introductionmentioning
confidence: 99%